Public R&D expenditure and their impact on private R&D: complementarity or substitution? Analysis for Central and East European countries - Mikołajczyk, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of this paper is to analyse the public R&D investments in Poland and other Central and East European (CEE) countries, especially their share in public expenditures and their impact on private R&D. To verify the research hypothesis that public and private R&D investments are complementary, panel regression models has been employed for data from the years 1999–2015. The main findings provide support for the complementarity hypothesis, both in Poland and other CEE countries. However, in Poland the positive impact of public expenditure on R&D on private expenditure on R&D is limited by the share of public R&D investments in the structure of total R&D investments. The main conclusions drawn from the CEE models are the lack of crowding‑out effect and the fact that public investments performed in public sector were the most growth‑friendly on condition that the share of public spending (vs. private) has been moderate.